Antioxidant activity of erlotinib and gefitinib: theoretical and experimental insights. (1st February 2022) - K. P, Safna Hussan; Babu, Thekkekara D.; C. M, Pareeth; Joshy, Greena; Mathew, Deepu; Thayyil, M. Shahin
Abstract: Erlotinib and gefitinib are quinazoline derivatives with antineoplastic properties. Usually, intake of antineoplastic agents results in much a greater degree of oxidative stress, i.e. the production of free radicals, than induced by cancer itself. Hence, anticancerous drugs must also exhibit antioxidant activity but this has not been studied thus far. In this study, the antioxidant activity of erlotinib and gefitinib was examined by experimental and computational studies. It was found that erlotinib and gefitinib exhibit good 2, 2-dipheny l-1-picrylhydrazyl (DPPH) radical and hydroxyl radical scavenging (HRS) activities. In DPPH assay, the IC50 for erlotinib and gefitinib were 0.584 and 0.696 mM, respectively, while IC50 for HRS assay were 0.843 and 1.03 mM for erlotinib and gefitinib, respectively. Structural characteristics such as frontier molecular orbitals (FMOs), molecular electrostatic potential maps (MESPs), and global descriptive parameters were calculated at DFT/B3LYP/6-311++G (d, p) on the optimized geometries of erlotinib and gefitinib. UV–visible spectroscopy revealed the possible electronic transitions between the FMOs and their associated excitation energies of both drugs and found that erlotinib has π to π* transitions while gefitinib has π to π* and σ to π* transitions. To elucidate the antioxidant activity of erlotinib and gefitinib, three mechanisms namely hydrogen atom transfer (HAT), single electron transfer proton transfer (SETPT), and sequential proton-loss electron-transfer (SPLET) were employed and articulated the results in arithmetic parameters like bond dissociation energy (BDE), proton affinity (PA), ionization potential (IP), electron transfer enthalpy (ETE), and proton dissociation enthalpy (PDE). Further, molecular docking studies have been carried out to have a better understanding of binding sites and modes of interaction with a well-known antioxidant target protein monoamine oxidase-B (MAO-B) employing docking scores and types of interactions. All the calculated parameters point out that though gefitinib and erlotinib were interchangeable, erlotinib requires a lesser amount of energy for proton transfer and electron transfer, moreover it scavenges radicals easily.